Ergonomic risk and its association with musculoskeletal disorders among computer users at Universiti Sains Malaysia, Health Campus - Amer, Shadi Shaddad Abdellatif (2024)
Computers are widely used in every field of modern society. It was the greatest invention of science that changed the lifestyle in the last two decade. In Malaysia, computer users have increased up to 85%. Furthermore, the range of computer use has been reported to be from 6 to 12 hours per day which can contribute to the development of Musculoskeletal Disorders (MSDs). This have been recognised as a threat to the health of the workers. Therefore, this study was conducted to determine the prevalence of MSDs and their association with ergonomic risk factors among computer users at the Universiti Sains Malaysia (USM) Health Campus, Kelantan. A cross-sectional study was conducted among three hundred and forty-six computer staff with 92% response rate. Participants were selected through random sampling method among those who fulfilled the inclusion criteria. Data were collected through self-report questionnaires using Cornell Musculoskeletal Discomfort Questionnaires and researcher direct observation by Rapid Office Strain Assessment (ROSA) to determine the ergonomic risk level for each workstation. The data were analysed using SPSS "Statistical Package for the Social Sciences" version 26 for descriptive, simple and multipl logistic regrision analyses. The mean of ROSA was 3.81(1.058). The prevalence of self-reported Work Related Musculoskeletal Disorder (WRMSDs) was 86.3%, 81% of the participants experiencing discomfort in the lower back (62.8%), right shoulder (53.4%), hip buttock (46.6%) and left shoulder (45.3%). Spearman’s correlation analysis revealed that left wrist MSDs (r = -0.018, p = 0.034), hip buttock MSDs (r = -0.116, p = 0.038), and left thigh MSDs (r = -0.124, p = 0.030), were significantly correlated with scores related to the use of mouse and keyboard, as well as the final ROSA score were significantly correlated with hip buttock MSDs (r = -0.114, p = 0.041) and left shoulder MSDs (r = 0.124, p = 0.027). Based on multiple logistic regression modelling, age was significantly associated with WRMSDs (Adjusted OR = 6.944, CI: 1.238-39.017, p = 0.028). Age and gender were significantly associated with neck MSDs (Adjusted OR = 3.908, 95% CI 1.342, 11.377, p = 0.012), (Adjusted OR = 2.042, 95% CI 1.199, 3.475, p = 0.009), respectively. Gender, age (51 - 60 years) , healthty and overweight (BMI) were significantly associated with right upper arm MSDs (Adjusted OR = 1.795, 95% CI 1.091, 2.950, p = 0.021), (Adjusted OR = 3.303, 95% CI 1.006, 10.849, p = 0.049), (Adjusted OR = 0.092, 95% CI 0.010, 0.814, p = 0.046), (Adjusted OR = 0.127, 95% CI 0.014, 1.123, p = 0.032), respectively. Only computer use (7 - 8 hours) was significantly associated with lower back MSDs (Adjusted OR = 2.045, 95% CI 1.149, 3.638, p = 0.015). In conclusion, computer users in USM Health Campus experienced high occurrence of MSDs in various parts of the body. Therefore, appropriate ergonomic and personal preventive control needs to be implemented to improve the health and wellbeing of the computer users on USM Health Campus.